Faktor Risiko Kejadian Kusta pada Anak di Kota Surabaya Tahun 2018 - Tating Nuraeni (Jurnal Kesehatan Manarang, 2018)
Leprosy is chronic and slowly progressive disease that is caused by Mycobacterium leprae. Leprosy firstly attacks nervous system, and then continue to attacks skin, mucosa, upper respiratory tract, reticular endothelial system, eyes, muscles and testes. Leprosy is known to occur at all ages ranging from infant to old age. The purpose of this study was to create a risk factors of incidences of leprosy among children in the city of Surabaya in 2018. This study applied an observational study design. Case and control groups were being compared in relation to past causes which might be relevant to the causes of leprosy. The sample in this study is part of the population because it is part of the subject in the cuplik to be observed and measured by the researchers. The sample is divided into two parts: the sample case and the control sample are 65 samples consisting of 13 cases and 52 controls. Sampling technique by total sampling. The results of this study showed that the history of BCG vaccine (P value = 0.706, OR = 1,265, CI: 0,37-4,29) and education of mother (P value = 0.385, OR = 1,728, CI: 0,49-5,98) did not affect the leprosy incidence in children in the city of Surabaya in 2018, while the contact history (P value = 0.000, OR = 13,567, CI: 2,68-68,6) had an effect on the incidence of leprosy in children in the city of Surabaya in 2018.